Cognitive Appraisals Mediate Affective Reactivity in Affiliative Extraversion - Inglis, Greig; Obonsawin, Marc C.; Hunter, Simon C. (Frontiers in Psychology, 2018)
Extraversion is comprised of two main components of affiliation and agency. Affiliative and agentic extraversion have been found to predict positive activation in response to appetitive stimuli, and affiliative extraversion also predicts warmth-affection in response to affiliative stimuli. The aim of this study was to test whether cognitive appraisals could account for these personality-emotion relationships. In an online experiment, 192 participants completed affiliative and appetitive imagery tasks, and reported their affect before and after each task. Participants also reported on how they appraised the imagined events. Affiliative extraversion was positively associated with warmth-affection following the affiliative imagery, and this relationship was mediated by appraisals of intrinsic pleasantness and compatibility with internal standards. Affiliative extraversion also predicted positive activation following the affiliative imagery, and this relationship was mediated by appraisals of importance. Neither agentic nor affiliative extraversion predicted any other form of affect following either the affiliative or appetitive imagery tasks. These results suggest that cognitive appraisals may be one mechanism that mediate affective reactivity in affiliative extraversion, although future confirmatory studies are required to further test this hypothesis.